Teaching Vocabulary by Using Experiential Learning to The Students of MTsN 2 Banda Aceh - Sariakin, Sariakin; Muchsin, Muchsin; Abdullah, Razali; Daud, Muslem; Mutia, Ratna (Universitas Serambi Mekkah, 2021)
The research aimed to find out if the students of MTsN 2 Banda Aceh who were taught vocabulary using experiential learning got a higher score than those who were taught without experiential learning. This research was conducted using pre-experiment with one class; pre-test and post-test design. The population of this research was the eighth-grade students. The total population of this study was 114 students composed of five classes; VIII-1, VIII-2, VIII-3, and VIII-4. Every class consists of about 28 students. The sample of this research was class VIII-1 of the eighth grade because the students’ ability of this class was better than the other classes. The data were taken through the test. Then, the obtained data were analyzed by using the gain score (GS). The result of this research showed that the GS was 0.32. Meaning that there was a difference between the students’ ability in mastering vocabulary before and after teaching using experiential learning and the difference was 0.32 points or 32%. Therefore, the student’s ability in mastering vocabulary increased 32% with experiential learning. Keywords: Teaching, Learning process, Experiential learning, Vocabulary.